Batman Forever? The Role of Trademarks for Reuse in the US Comics Industry - Franziska Kaiser; Alexander Cuntz; Christian Peukert (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study how trademarks affect reuse of creative works in the comics industry. As a creative industry, the comics industry systematically relies on copyrights. But trademark protection can also be exploited to generate income from the reuse of comic characters or to strategically exclude others from reuse. Our unique data set combines US trademark records of comic characters with information on reuse in print media and franchise products from 1990 to 2017. We find that, on average, additional trademark protection is associated with a reduction in reuse in printed comic books of about 19%. We highlight three mechanisms: first, the negative relationship between trademarking and reuse has been especially pronounced since the early 2000s, when the arrival of digital technologies lowered the costs of entry, promotion, and distribution. Second, our results are driven by less reuse by third parties, not trademark holders. Third, reuse is higher when trademark owners license comic characters to third parties. The negative association between trademarking and reuse carries over to franchise products, but it is weaker and tied to the era of digitization, with a 2% decline in reuse in franchise movies and 9% lower reuse in video games.
Keywords: O31; O34; L82; Z11; 330; comics; trademarks; intellectual property rights; digitization